Development and Validation of Payment Performance Assessment Tool for Construction Industry - Abdullahi Sarki, Sani; Adul-Hamid, Razali; W.Y.W, Mahmood (International Journal of Engineering and Technology, 2018)
The late payment has been the major issues facing the construction industry across the globe. Many studies have looked at this issues from management and legal perspectives. Despite its endemic effect on the construction industry, there is no any assessment tools for measuring the payment performance (late and prompt payment). This paper developed and validated a payment performance assessment tool in the context of construction industry client organization, particularly in the Nigerian construction industry. The tool was developed based on the organizational culture and payment performance attributes for the client organization. Analytical Hierarchy Process (AHP) was used to elicit pair-wise comparison and weight of each variable. This led to the development of the tool. The tool was then validated in the assessment of clientâ€™s payment performance of a case organization. The assessment tool was calibrated based on consensus benchmarking. However, the calibration ranges from 0.00-0.69 as late payment performance, 0.70-0.98 prompt payment performance and 0.99-1.00. Absolute prompt payment performance. The result shows that the payment assessment tool succeeded in measuring payment performance of a case organization with a score of 0.50 points indicating that the organization do not pay its contractors on time. Therefore, the organization is experiencing late payment. However, there is need to replication the study to revalidate the tool in another organization or country.Â Â